2016
DOI: 10.1080/2162402x.2016.1256528
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived osteopontin isoforms cooperate with TRP53 and CCL2 to promote lung metastasis

Abstract: The lungs are ubiquitous receptacles of metastases originating from various bodily tumors. Although osteopontin (SPP1) has been associated with tumor dissemination, the role of its isoforms in lung-directed metastasis is incompletely understood. We employed syngeneic mouse models of spontaneous and induced lung-targeted metastasis in C57BL/6 mice competent and deficient in both Spp1 alleles. Tumorderived osteopontin expression was modulated using either stable anti-Spp1 RNA interference, or forced overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 50 publications
(69 reference statements)
2
44
0
Order By: Relevance
“…Indeed, numerous such cells co-expressing CCR2 and IL-1β were identified in the stromata of our experimental KRAS -mutant tumors by immunohistochemistry (Figure 5B). To definitively test our hypothesis, we induced flank tumors by injecting one million LLC cells ( Kras G12C ) sc into syngeneic C57BL/6 mice competent ( WT ) or deficient ( Il1b -/- , Ccr2 -/- ) [16, 18] in the Il1b and Ccr2 genes. Mice haplo/diplo-insufficient in the Cxcr1 and Cxcr2 chemokine receptor genes ( Cxcr1 -/- , Cxcr2 +/- ) [15] were also employed as additional controls for Ccr2 -/- mice and daily ip saline or 15 mg/Kg deltarasin treatments were initiated when tumors reached 100 mm 3 volumes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, numerous such cells co-expressing CCR2 and IL-1β were identified in the stromata of our experimental KRAS -mutant tumors by immunohistochemistry (Figure 5B). To definitively test our hypothesis, we induced flank tumors by injecting one million LLC cells ( Kras G12C ) sc into syngeneic C57BL/6 mice competent ( WT ) or deficient ( Il1b -/- , Ccr2 -/- ) [16, 18] in the Il1b and Ccr2 genes. Mice haplo/diplo-insufficient in the Cxcr1 and Cxcr2 chemokine receptor genes ( Cxcr1 -/- , Cxcr2 +/- ) [15] were also employed as additional controls for Ccr2 -/- mice and daily ip saline or 15 mg/Kg deltarasin treatments were initiated when tumors reached 100 mm 3 volumes.…”
Section: Resultsmentioning
confidence: 99%
“…NCI-H358, NCI-H358M, NCI-H460, NCI-H520, NCI-H1299, NCI-H1944, NCI-H3122 (referred to hereafter omitting NCI), EKVX, A549, LLC, B16F10, and PANO2 cell lines were from the National Cancer Institute (Frederick, MD); MC38 cells were a gift from Dr. Timothy S. Blackwell (Vanderbilt University, Nashville, TN) and AE17 cells from Dr. YC Gary Lee (University of Western Australia, Perth, Australia) [1315]. FULA1 ( FVB urethane-induced lung adenocarcinoma 1) and CULA ( C57BL/6 urethane-induced lung adenocarcinoma) cell lines were isolated from the lungs of FVB and C57BL/6 mice, respectively, harboring primary lung adenocarcinomas induced by urethane [13,16,17]. Human and murine cell lines were cultured, respectively, in Roswell Park Memorial Institute (RPMI)-1640 and Dulbecco’s Modified Eagle Medium (DMEM), both supplemented with 10% FBS and 100 IU/mL penicillin/streptomycin, and were maintained in a humidified incubator at 37 °C with 95% air–5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We subsequently cross-examined the transcriptomes of LUAD cell lines isolated from urethaneinduced lung tumors [34,35] and of their originating murine lungs with the gene expression profiles of murine AEC isolated from tracheal explants, of murine ATII cells [36], and of murine bone- Similar analyses of the transcriptomes of human LUAD and corresponding healthy lungs [37] and the profiles of primary human AEC, ATII cells, and AMΦ [38][39][40], also disclosed that the AEC (but not the ATII and AMΦ) signature was significantly enriched in LUAD compared with healthy lung tissue ( Figure 6C and 6D). Gene set enrichment analyses showed that while AEC, ATII, and BMDM signatures were significantly enriched in murine lungs, the AEC signature predominated over ATII and BMDM signatures in LUAD cells.…”
Section: Enrichment Of Airway and Alveolar Signatures In Experimentalmentioning
confidence: 99%
“…Lung tumors were dissected from surrounding healthy lung parenchyma under sterile conditions, minced into 1-mm pieces, and cultured at 37 0 C in 5% CO2-95% air using DMEM 10% FBS, 2 mM L-glutamine, 1 mM pyruvate, 100 U/mL penicillin, and 100 U/mL streptomycin. All cell lines were immortal and indefinitely phenotypically stable over > 18 months and/or 60 passages, and were tumorigenic and metastatic in C57BL/6 mice [34,35].…”
Section: Urethane-induced Lung Adenocarcinoma Cell Linesmentioning
confidence: 99%